Pemanfaatan Minyak Jelantah Menjadi Lilin Aromaterapi Guna Mengurangi Pencemaran Lingkungan Desa Tlahap - Labib, Ahmad; Nasikah, Siti; Karim, Abdul; Aliyah, Nadiasofiyatul; Kamaliyah, Rizqi; Umam, Saikhul; Majid, Muhammad Khamidum; Siroj, Ahmad Mustofa Aqil; Mufidah, Inayatul; Al Ihwan, Maula; Rahman, Tsabit Zada; Azani, Faidah Rizki; Rohmah, Ayu Aeni; Khotimah, Khusnul (LPPM Sekolah Tinggi Islam Kendal, 2026)
Tlahab Village is a village in Gemuh District, consisting of three sub-district units (RW) and thirteen community units (RT). Given its population, used cooking oil produced by households in Tlahab Village is a type of waste with potential economic value. The transformation of used cooking oil into aromatherapy candles not only creates new business opportunities but also has a positive impact on the environment. In this article, the author uses a qualitative research method with a descriptive-explanatory approach that aims to provide a clear picture of the aromatherapy candle making program implemented during the Real Work Program, including a detailed explanation of the production stages. The implementation of the aromatherapy candle making workshop from used cooking oil yielded positive results. This program not only contributes to reducing the impact of household waste but also provides economic and social benefits to the Tlahab Village community. Used cooking oil, previously considered only as waste that pollutes the environment, has now been successfully processed into functional products with economic value.